2020
DOI: 10.1063/5.0026956
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Hall effect and negative longitudinal magnetoresistance in half-Heusler topological semimetal candidates TbPtBi and HoPtBi

Abstract: Half-Heusler compounds have attracted significant attention because of their topologically non-trivial electronic structure, which leads to unusual electron transport properties. We thoroughly investigated the magnetotransport properties of high-quality single crystals of two half-Heusler phases, TbPtBi and HoPtBi, in pursuit of the characteristic features of topologically non-trivial electronic states. Both studied compounds are characterized by the giant values of transverse magnetoresistance with no sign of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 62 publications
3
10
0
Order By: Relevance
“…Previous studies suggest that large anomalous Hall angle of TbPtBi results from large net Berry curvature induced by Weyl points or anti-crossing of spinsplit bands. [25][26][27][28] In our study, as suggested by DFT calculation results shown in Figure 1c, the large net Berry curvature at Fermi level is mainly contributed by Weyl points. To further confirm this point, we performed measurement on longitudinal magneto-resistance (LMR) (Figure 3a,b) and planar Hall resistance (PHE) (Figure 3c,d).…”
Section: Topological Band and Bipolar Effect Enhanced S Yx (B)supporting
confidence: 72%
See 2 more Smart Citations
“…Previous studies suggest that large anomalous Hall angle of TbPtBi results from large net Berry curvature induced by Weyl points or anti-crossing of spinsplit bands. [25][26][27][28] In our study, as suggested by DFT calculation results shown in Figure 1c, the large net Berry curvature at Fermi level is mainly contributed by Weyl points. To further confirm this point, we performed measurement on longitudinal magneto-resistance (LMR) (Figure 3a,b) and planar Hall resistance (PHE) (Figure 3c,d).…”
Section: Topological Band and Bipolar Effect Enhanced S Yx (B)supporting
confidence: 72%
“…Due to large net Berry curvature at the Fermi level, TbPtBi exhibits large anomalous Hall conductivity and anomalous Hall angle (Figure S3, Supporting Information), which further enhances total Hall angle (Figure 1d) and are consistent with previous reports. [25][26][27][28] Moreover, the maximum total Hall angle of ≈3 at 2 K and 14 Tesla is larger than previous reports [25][26][27][28] and some other magnetic topological materials, such as Co 3 Sn 2 S 2 , Mn 3 Ge, and GdPtBi. [29][30][31] Based on Mott formula and linear response equation, the transverse thermopower can be expressed as [32] In the case where Hall angle is energy dependent, taking a first-order approximation of above formula, the transverse thermopower can be rewritten as…”
Section: Unique Features Of Tbptbi For High Te Performancementioning
confidence: 60%
See 1 more Smart Citation
“…This leads to large anisotropic magnetoresistance (AMR = [ρ(90 • ) − ρ(0 • )]/ρ(0 • )) which is equal to −95% for WSi 2 and −98% for MoSi 2 at T = 2 K and in B = 14 T. The magnitudes of AMR are larger than those we reported previously for rare earth monoantimonides [16,49] and half-Heulser bismuthides. [72][73][74] The origin of this huge AMR can be ascribed to the highly anisotropic Fermi surface of the studied compounds. Large AMR has been previously observed in materials with XMR, like bismuth, [75] graphite [76] and WTe 2 .…”
Section: Effect Analysis (See Supplementary Information)mentioning
confidence: 97%
“…For example, it is very pronounced in RFe 2 and RCo 2 Laves phases [6,7] (R = rare earth), where it could be satisfactorily explained by means of single-ion crystal-field theory [8]. From more recent examples, strong anisotropy in the fieldangular dependence of magnetoresistance, measured upon continuously rotating the direction of an external magnetic field B, was reported for the half-Heusler compounds TbPtBi and HoPtBi [9,10] and for several RE dodecaborides [11][12][13][14][15][16][17], most prominently pure and doped TmB 12 and ErB 12 . In TmB 12 and its doped derivatives Tm 1−x Lu x B 12 and Tm 1−x Yb x B 12 , the field-angular magnetic phase diagrams in the B ⊥ 110 plane, suggested by the magnetotransport measurements, resemble a Maltese cross [12][13][14][15][16][17] with very sharp straight transition lines, separating different antiferromagnetic (AFM) phases that exist between 0 and 3 T in sectors around the [001], [111], and [110] field directions.…”
Section: Introduction a Magnetic Anisotropy In Cubic Systemsmentioning
confidence: 99%